(untitled) (Stavební obzor - Civil Engineering Journal, 2024)
This study explores the fracture energy of unstabilized rammed earth, focusing on the influence of different types and amounts of clay within the mixtures. Utilizing a three-point bending test, this research evaluates the fracture energy of rammed earth to better understand how variations in clay type and content affect its structural integrity. The findings reveal significant differences in fracture energy values correlated with the clay’s molecular structure and the interlayer chemical bonds. Clays such as illitic-kaolinitic, montmorillonite, and illite were tested, each demonstrating unique responses to mechanical stress based on their respective chemical bonds. Mixtures containing illitic-kaolinitic clay exhibited the highest fracture energy values, attributed to the presence of kaolinite due to its robust interlayer bonds. The results contribute insights into the selection and optimization of rammed earth materials for sustainable construction, aligning with the growing emphasis on ecological and durable building resources.